Orientação ao consumidor e performance : uma análise qualitativa sobre os motivos da relação - Antonio , Paloma (2015)
Customer orientation is the set of organizational beliefs which determine the prioritization of the client in front of other matters (DESHPANDÉ, FARLEY, WEBSTER; 1993) and the literature highlights the positive influence of this strategic orientation on several types of organizational performance. However, some papers have demonstrated results rather non significant and even negative suggesting the need for a deeper analysis, and the scientific community still has not brought a qualitative analysis on the motives which establish the relationship between customer orientation and superior performance. This study is based on the need to explore this relationship, consolidating the already known motives and investigating probable new explanations. With the objective of identifying and comprehending the motives for the relationship between customer orientation and performance, the research was conducted in three phases: literature review with the analysis of 44 articles about this relationship, execution of twenty in-depth interviews with academic and market experts and, ultimately, the confrontation of the motives pointed by the interviewees with the ones presented by the literature.It was possible to identify explanations that haven’t been explored by the scientific community yet, such as the appreciation of the marketing role inside organizations, the ability to develop a global view of the consumer, the focus on effectiveness and the capacity to educate the consumer. At the end, the reader shall have a comprehension of the suggested direction for the customer oriented companies to reach superior performance, through frameworks of motives for the relationship between customer orientation and performance.